Pengaruh Penerapan Metode Tanya Jawab Terhadap Peningkatan Hasil Belajar Siswa Kels IV MI Pada Mata Pelajaran Fiqih di MI Persis 259 Firdaus Pangalengan - Endar Pratama Sopian (PIJAR: Jurnal Pendidikan dan Pengajaran, 2023)
This research generally aims to see the application of the question and answer method of learning as an effort to improve student learning outcomes in Fiqh lessons. Learning is a process or a person's efforts to gain additional knowledge, understanding, skills and attitudes, which are the result of interaction with the environment. One way to see whether the learning process is effective or not is to carry out learning evaluation activities, where students' abilities can be measured whether they have met the teacher's expectations or not. In this study the focus is on testing the theory (quantitative), hypotheses are formulated from the framework of thinking in the form of statements. Technically, the process is known as operationalization. The hypothesis is a temporary answer to the research questions posed to the problems that have been tested. The clarity of the relationship will make it easier for the statistical test model to be used. In this study, the temporary conclusion from the observations was that there was an effect of the application of the question and answer method on improving the learning outcomes of MI students in fiqh subjects at MI Persis 259 Firdaus Pangalengan